Construction of the content extraction signature scheme based on the thought of the batch scheme - Zixin TANG; Xinyi HUANG (网络与信息安全学报)
The Waters scheme was transformed into the content extraction signature scheme at the bridge of the thought from the batch signature scheme.The proposed scheme is improved by the RSAProd scheme,presented by Steinfeld,Bull,Zheng (ICISC 2001).The operation time is saved in every stage at the slight sacrifice of the length of extraction signatures.The security was proved that the proposed scheme is existentially unforgeable under chosen message attacks while the privacy is maintained.